Bilateral Investment Treaty and Foreign Direct Investment in India: A Dynamic Panel GMM Estimation of Causal Effects - T., Lakshmanasamy (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
India has one of the largest Bilateral Investment Treaty (BIT) networks with other counties around the world. The BITs is to promote foreign investment by increasing investor confidence, empowering individual private parties to take international arbitral proceedings against the threat of appropriation by the government of the host country. This paper analyses the effect of BITs on FDI inflows in India using panel data for 76 countries for the time period 2000-2016 applying a dynamic panel generalised method of moments instrumental variable estimation method. The differenced GMM and system GMM estimates show a significant negative effect of bilateral investment treaties on the FDI inflows in India. While the lagged FDI has a significant positive effect, the financial openness of the source nations is reducing FDI inflows to India. The POLCON index shows that the countries with lesser political constraints have positive FDI outflow towards India. As opposed to domestic variables, the Chinn-Ito and POLCON indices have a greater share of change in FDI inflows to India. It seems that the BITs is not efficient enough to create investor confidence to invest in India.